2017
DOI: 10.1080/07399332.2017.1360302
|View full text |Cite
|
Sign up to set email alerts
|

Maternal determinist of term intrauterine growth restriction (IUGR) in the Kingdom of Saudi Arabia

Abstract: Intrauterine growth restriction was defined as occurring if birth weight of the newborn is below 10 percentile for gestational age. We investigated its maternal determinants in Riyadh, Saudi Arabia by comparing 76 cases to 76 controls to aid in early detection, diagnosis and proper prevention. A history of stillbirth, less than three years interpregnancy intervals, experiencing preeclampsia during pregnancy besides gaining less than nine kilograms during term pregnancy would signal a risk of having intrauterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
2
0
2
Order By: Relevance
“…Pada wanita dengan berat badan ratarata atau rendah, kurangnya pertambahan berat badan selama hamil dapat menimbulkan pertumbuhan janin terhambat. Kurangnya pertambahan berat badan pada trimester ke dua berkolerasi kuat dengan [12]. Namun jika ibu berperawakan besar atau sehat, penambahan berat badan di bawah rata-rata tanpa penyakit pada ibu tidak mungkin disertai hambatan pertumbuhan janin yang bermakna.…”
Section: Status Giziunclassified
“…Pada wanita dengan berat badan ratarata atau rendah, kurangnya pertambahan berat badan selama hamil dapat menimbulkan pertumbuhan janin terhambat. Kurangnya pertambahan berat badan pada trimester ke dua berkolerasi kuat dengan [12]. Namun jika ibu berperawakan besar atau sehat, penambahan berat badan di bawah rata-rata tanpa penyakit pada ibu tidak mungkin disertai hambatan pertumbuhan janin yang bermakna.…”
Section: Status Giziunclassified
“…1 No. 1 Oktober 2020 E-ISSN XXXX-XXXX penurunan berat lahir [12]. Namun jika ibu berperawakan besar atau sehat, penambahan berat badan di bawah rata-rata tanpa penyakit pada ibu tidak mungkin disertai hambatan pertumbuhan janin yang bermakna.…”
Section: Status Giziunclassified
“…IUGR is relatively common in Saudi Arabia; however, few studies have investigated the role of the placenta in IUGR. A study performed in Arar City, northern Saudi Arabia, revealed a significant increase in syncytial knots and capillaries of terminal villi of IUGR placentas compared to the control group ( Abdrabbo and Alrashed 2017 ). In another study performed in Al-Madinah Almonawarah City, western Saudi Arabia, investigators observed a significant correlation between IUGR and placental arterial narrowing, degeneration, decreased number of arteries in stem villi, decreased number of terminal villous capillaries, and villitis ( Almasry, Eldomiaty, Elfayomy, Habib and Safwat 2012 ).…”
Section: Introductionmentioning
confidence: 98%
“…IUGR affects 30 million neonates yearly worldwide ( Sharma et al, 2016 , Abdrabbo and Alrashed, 2017 ). Studies have revealed that IUGR can lead to various diseases in the future, including diabetes, cardiovascular disorders, hypertension, and emotional/behavioral disorders ( Cosmi et al, 2011 , Saleem et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%